2020
DOI: 10.1186/s12871-020-01133-4
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided versus Shikani optical stylet-aided tracheal intubation: a prospective randomized study

Abstract: Background: To compare ultrasound-guided tracheal intubation (UGTI) versus Shikani optical stylet (SOS)-aided tracheal intubation in patients with anticipated normal airway. Methods: Sixty patients aged 18-65 years old who presented for elective surgery under general anesthesia were recruited in this prospective randomized study. They were assigned into two equal groups, either an ultrasoundguided group (Group UG, n = 30) or an SOS-aided group (Group SOS, n = 30). After the induction of anesthesia, the trachea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Video-assisted intubating stylet technique, using the Shikani method of intubation [ 4 ], has been gaining popularity in many medical centers in Taiwan and around the world in recent years [ 6 , 7 , 8 , 9 , 10 ]. Studies in the literature have shown that the mean time to carry out intubation when using the Shikani stylet was 42.4 s [ 21 ] and 58 s [ 22 ]; however, this includes operators who are still in the learning curve and/or are not quite experienced with the Shikani stylet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Video-assisted intubating stylet technique, using the Shikani method of intubation [ 4 ], has been gaining popularity in many medical centers in Taiwan and around the world in recent years [ 6 , 7 , 8 , 9 , 10 ]. Studies in the literature have shown that the mean time to carry out intubation when using the Shikani stylet was 42.4 s [ 21 ] and 58 s [ 22 ]; however, this includes operators who are still in the learning curve and/or are not quite experienced with the Shikani stylet.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the use of PPE, safe methods and protocols to conduct tracheal intubation procedures on COVID-19 patients are of paramount importance. Besides the conventional direct laryngoscopy and videolaryngoscopy, a “seeing” intubating stylet technique for tracheal intubation has been pioneered by Shikani [ 4 ] and modified by Levitan [ 5 ] decades ago, and numerous articles have been published on thousands of patients detailing the safety and advantages of the Shikani video-assisted optical stylet tracheal intubation method [ 6 , 7 , 8 , 9 , 10 ]. To our knowledge, this report describes for the first time the use of the Shikani video-assisted intubating stylet and technique to safely conduct tracheal intubation in a patient with a fatal COVID-19 infection in a negative pressure isolation room environment.…”
Section: Introductionmentioning
confidence: 99%
“…This technique was later reported by Moustafa et al to be 99%, 132/133 (72%, 96/133 on the first attempt) effective needing 57 s in adult patients [41]. This high efficacy was later confirmed by Ma et al, who found a 93.3% (28/30) success rate [42].…”
Section: Ultrasound Guided Tracheal Intubationmentioning
confidence: 78%
“…All studies used a hypoechoic shadowing and widening of the vocal cords in transversal view as proof of endotracheal intubation [41][42][43].…”
Section: Ultrasound Guided Tracheal Intubationmentioning
confidence: 99%
“…Several studies provide promising results about the high pooled sensitivity (about 98%) and specificity (about 97%) of POCUS in confirming ETI 15–17. Real-time POCUS further extends to assist ETI 18 19. Notably, POCUS provides a view independent of laryngoscopy or bronchoscopy, making it possible to combine the outside with the inside visualisation 13.…”
Section: Introductionmentioning
confidence: 99%